Potential Owner-Related Risk Factors That May Contribute to Obesity in Companion Dogs in Aotearoa New Zealand. - Forrest R; Awawdeh L; Esam F; Pearson M; Waran N (MDPI (Basel, Switzerland), 2022)
Approximately a third of all Aotearoa New Zealand (NZ) households include a dog, with 28% of these dogs being overweight or obese, conditions that are associated with many serious health issues. Therefore, healthy weight interventions that focus on the owner's role are of great importance to companion animal welfare in NZ. Accordingly, the present study explores the feeding practices associated with NZ dogs and identifies potential owner-related risk factors contributing to these animals being overweight or obese. The current study used data collected from a survey conducted online in 2019 between January and March of NZ residents over 18. Along with demographic questions, the respondents were asked questions regarding their dog's body condition and diet questions related to the body. Nearly a quarter (26%, n = 609) of the survey participants (n = 2358) owned at least one dog. The current study reported that increasing age range, household income and the number of children increased the likelihood of having a dog while increasing qualification level and living in a town/city decreased the likelihood. The majority of the respondents fed their dog(s) treats (59%) and 85% fed them specialised food bought from a pet shop, veterinary clinic and/or different online sources. Just over a third of the participant (39%) reported that they fed their dog(s) biscuits from the supermarket, 36% fed their dog(s) raw meat, and 34% of respondents fee their dog(s) table scraps/human food. These results suggest that many dog owners feed their dog(s) various food types, making it a challenging task to determine the exact amount required from each type in order not to exceed caloric intake. Disagreement regarding the correct body condition were reported among twenty per cent of the respondents. This finding indicates a knowledge gap among the NZ dog-owning population that may negatively affect their dogs' welfare and wellbeing. Future research into pro-equity approaches to address these issues is needed so that dogs in NZ can live not only a good life but also their best life.
Keywords: Aotearoa; New Zealand; canine; companion animal; diet; dog; dog–owner relationship; human behaviour; obesity; pet